THU0492 EFFICACY OF US-GUIDED HYALURONIC ACID INJECTIONS IN ACHILLES AND PATELLAR MID-PORTION TENDINOPATHIES: A PROSPECTIVE MULTICENTRIC CLINICAL TRIAL. (June 2019) - Frizziero, Antonio; Vittadini, Filippo; Oliva, Francesco; Vetrano, Mario; Vulpiani, Maria Chiara; Giordan, Nicola; Masiero, Stefano; Maffulli, Nicola
Abstract : Background: Achilles and patellar tendinopathies are common clinical conditions that determine chronic pain and functional impairment. Conservative treatment can be effective, but it is time-consuming and it requires intensive patient compliance. Hyaluronic acid (HA) is a key component of the extracellular matrix, and its anti-inflammatory, lubricant and analgesic properties are well established in osteoarthritis. Growing pre-clinical evidence point toward a possible role of HA in the management tendon pathology, while clinical evidences are still lacking. Objectives: The primary objective was to assess the efficacy of a new formulation of HA (20 mg/2 ml; 500-730 kDa), obtained from biofermentation, in function improvement on VISA-A and VISA-P scores at 90 days of follow-up in patients with Achilles or patellar tendinopathy. Secondary objectives were to evaluate improvement in pain (NRS-11), US parameters (tendon composition and neovascularization), and quality of life (EQ-5D). Safety of this new HA formulation was also evaluated. Methods: This was a prospective, open-label, multicenter clinical trial. Thirty-five patients (25in AT group; 9 patients in PT group), who satisfied strict inclusion and exclusion criteria, were recruited over a 4-month period. Each patient received 1 injection weekly for 3 weeks under US-guidance at the painful site of tendinopathy, and was evaluated at 14, 45 and 90 days after the procedure. Subjects were instructed to record on a diary any intake of the permitted rescue medication for pain relief (i.e. paracetamol up to 3 g per day) throughout the study period and to interrupt treatment at least 24 hours prior to each visit. Results: Significant improvement on VISA-A (23.22±23.17; 95% CI: 13.20; 33.24; p<.0001) occurred, and improvement on VISA-P was also revealed (19.25±11.61; 95% CI: 9.54; 28.96; p=0.0022). NRS-11 score significantly decreased in the AT group (4.52±3.25; 95% CI: -5.93; -3.12; p<0.0001) and in the PT group(-4.75±3.20; 95% CI: -7.42; -2.08; p=0.0040). Significant improvement of US parameters in the AT group was evidenced (McNemar's test; p=0.0016 and p=0.0114, respectively), while in the PT group the presence of these clinical symptoms showed only a tendency to decrease (p=0.3173 for both). EQ-5D-5L total score tended to increase in both the AT and PT groups (mean change vs. baseline at day 90 equal to 15.96±18.95 (range: -50; 45) and 15.50±32.42 (range: -40; 71), respectively). Conclusion: Three US-guided HA injections may improve pain and function in patients with Achilles and patellar tendinopathy for up to 90 days of follow-up. Amelioration in tendon structure, neovscolarization and clinical parameters may also be achieved. The hyaluronic acid injection was also safe and well tolerated. References: [1] Frizziero A, Salamanna F, Giavaresi G, Ferrari A, Martini L, Marini M, Veicsteinas A, Maffulli N, Masiero S, Fini M. Hyaluronic acid injections protect patellar tendon from detraining-associated damage. Histol Histopathol. 2015 Sep;30(9):1079-88 [2] Lynen N, De Vroey T, Spiegel I, Van Ongeval F, Hendrickx NJ, Stassijns G. Comparison of Peritendinous Hyaluronan Injections Versus Extracorporeal Shock Wave Therapy in the Treatment of Painful Achilles' Tendinopathy: A Randomized Clinical Efficacy and Safety Study. Arch Phys Med Rehabil. 2017 Jan;98(1):64-71 Disclosure of Interests: Antonio Frizziero: None declared, Filippo Vittadini: None declared, Francesco Oliva: None declared, Mario Vetrano: None declared, Maria Chiara Vulpiani: None declared, Nicola Giordan Employee of: Fidia Farmaceutici, Stefano Masiero: None declared, Nicola Maffulli: None declared